Optical multi-bound solitons - Binh, Le Nguyen (Optics and photonics (Boca Raton, Fla.), 2015)
Optical Multi-Bound Solitons describes the generation and transmission of multi-bound solitons with the potential to form the basis of the temporal coding of optical data packets for next-generation nonlinear optical systems. The book deals with nonlinear systems in terms of their fundamental principles, associated phenomena, and signal processing applications in contemporary optical systems for communications and laser systems, with a touch of mathematical representation of nonlinear equations to offer insight into the nonlinear dynamics at different phases. The text not only delineates the strong background physics of such systems but also: Discusses the phase evolution of the optical carriers under the soliton envelopes for the generation of multi-bound solitons Explains the generation of multi-bound solitons through optical fibers Examines new types of multi-bound solitons in passive and active optical resonators Conducts bi-spectral analyses of multi-bound solitons to identify the phase and power amplitude distribution property of bound solitons Presents experimental techniques for the effective generation of bound solitons Optical Multi-Bound Solitons provides extensive coverage of multi-bound solitons from the dynamics of their formation to their transmission over guided optical media. Appendices are included to supplement a number of essential definitions, mathematical representations, and derivations, making this book an ideal theoretical reference text as well as a practical professional guidebook.